2021
DOI: 10.2147/nss.s301113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dinner Timing on Sleep Stage Distribution and EEG Power Spectrum in Healthy Volunteers

Abstract: Eating time and sleep habits are important modifiable behaviors that affect metabolic health, but the relationship between food intake and sleep remains incompletely understood. Observational data suggest that late food intake is associated with impaired sleep quality. We examined the effect of routine dinner (RD, 5 hours before bedtime) vs late dinner (LD, 1 hour before bedtime) on sleep architecture in healthy volunteers. Participants and Methods: This was a post hoc analysis of a randomized crossover study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Diet is also widely considered an important modifiable factor that has been often proposed to improve sleep duration and quality [ 22 ]. Eating schedules, food intake, and energy balance altered the propensity for sleep and sleep architecture [ 23 ]. Adults consuming proinflammatory diets are more likely to have a short or long sleep duration, and/or self-reported sleep disturbances [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diet is also widely considered an important modifiable factor that has been often proposed to improve sleep duration and quality [ 22 ]. Eating schedules, food intake, and energy balance altered the propensity for sleep and sleep architecture [ 23 ]. Adults consuming proinflammatory diets are more likely to have a short or long sleep duration, and/or self-reported sleep disturbances [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the timing of eating, regardless of its composition, may contribute to circadian system misalignment, directly affecting sleep, as well as weight status and metabolic health. [22][23][24][25][26][27] Some observational studies have shown that eating close to bedtime was associated with impaired sleep quality. [22][23][24] On the other hand, a randomized crossover study found that shifting dinner timing from 5 hours before sleep to 1 hour before sleep in healthy volunteers did not result in significant adverse changes in overnight sleep architecture.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Some observational studies have shown that eating close to bedtime was associated with impaired sleep quality. [22][23][24] On the other hand, a randomized crossover study found that shifting dinner timing from 5 hours before sleep to 1 hour before sleep in healthy volunteers did not result in significant adverse changes in overnight sleep architecture. 24 It is important to emphasize that one relevant aspect of meal timing studies is to define what a late meal is, 25 and it seems that the clock timing by itself may not be useful to study metabolic alterations related to evening meal timing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, there was an association between LD consumption and nocturnal metabolic disorders, especially in habitual earlier sleepers. In addition, the same authors examined the effect of RD and LD consumptions on sleep quality (3) . Although there was no significant difference in overnight sleep architecture, LD caused a 2•5 % initial increase in delta power and a reciprocal 2•7 % decrease in combined α and β power, presenting that LD was associated with deeper sleep in the beginning of the night.…”
mentioning
confidence: 99%